PERFORMANCE OF FIBRE REINFORCED MORTAR INCORPORATING PALM OIL FUEL ASH - Mohd Syukry, Saiful (Universiti Malaysia Sarawak (UNIMAS), 2021)
Fibre Reinforced Concrete (FRC) is a mixture of concrete and fibres which has displayed a significant improvement in developing the mechanical properties of concrete over the years. FRC has also shown improvement in the cracking parameters in terms of toughness and cracking length with concrete composite containing partial cement replacement such as Fly Ash (FA) and Silica Fume (SF). Meanwhile, Palm Oil Fuel Ash (POFA) is another cement replacement material which is a waste product from palm oil manufacturing. Concrete was known as a brittle material, which its behaviour under loading is completely different from that of ductile material such as steel. Due to the potentials of POFA in concrete which have enhanced the mechanical properties of concrete especially related to compressive strength and workability, this research aims to explore the mechanical behaviour of Fibre-Reinforced Mortar (FRM) mixed with micro-fine size Treated Palm Oil Fuel Ash (POFA). This research is mainly to determine the optimal amount of POFA with Fibre in mortar and the displacement ductility ratio of the samples. Fibre ranges from 0 kg/m3 to 20 kg/m3 and concrete replacement with POFA ranges from 0% to 60% was experimented. From the compressive strength results, it can be deduced that sample with 40% POFA inclusion mixed with 10 kg/m3 poly propylene fibres gives higher strength compare to 100% OPC mixed with 10 kg/m3 poly propylene fibres. While from the flexural test, samples with 40% POFA inclusion mixed with 15 kg/m3 and 10 kg/m3 poly propylene fibres give the highest ductility ratio which are 7.8 and 13.3 at 56 days of curing ages respectively. Scanning Electron Microscopy (SEM) was done to observe the surface morphology of the fibre reinforced mortar. Based on the results and observations from various POFA inclusions with 10, 15, and 20 kg/m3 of poly propylene fibres, impressive results were obtained on the mechanical strength for 40% POFA with additions of 10 iv kg/m3 and 15 kg/m3 of poly propylene fibres. It can be decided that the inclusion of POFA can improve the strength properties of the mortar in term of compressive strength while, fibres can enhance the tensile properties of the mortar which is beneficial in minimizing the usage of Ordinary Portland Cement (OPC) and Steel Bar Reinforcement.